ANALYSIS OF SISKEUDES (VILLAGE FINANCIAL SYSTEM) WITH TAM APPROACH (TECHNOLOGY ACCAPTANCE MODEL) - Desy Nur Pratiwi; Yuwita Ariessa Pravasanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The government has provided village fund assistance since 2015 aimed at developing village governance. The allocation of village funds is a form of financial decentralization by the government towards an independent village. The purpose of this study is to determine the factors that influence the acceptance of the Siskeudes application using the TAM (Technology Accaptance Model) approach. The data used are primary data in the form of a questionnaire given to village financial managers in Sukohajo Regency. The number of questionnaires processed in this study were 34 questionnaires. Hypothesis testing is done by using multiple linear regression. The results show that usability has an effect on the use of Siskeudes, but convenience does not affect the use of Siskeudes. From these results, it means that TAM research only focuses on the question of the utility and effectiveness of a system for task completion. Keywords: Siskeudes, Perceived Usefulness , Perceived Ease of Use